2018
DOI: 10.1002/adom.201800961
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Crystal Pancharatnam–Berry Micro‐Optical Elements for Laser Beam Shaping

Abstract: Shaping the intensity profile of a laser beam is desired by various industrial applications. In this paper, a new approach is presented to design and fabricate liquid crystal (LC) micro‐optical elements (MOEs) with engineered Pancharatnam–Berry (PB) phases for beam shaping. By generalizing the Snell's law for spatially variant PB phases, molecular orientation patterns are designed for the liquid crystal MOEs to shape a Gaussian laser beam into flattop intensity profiles with circular and square cross‐sections,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…[44,48] This PB phase can be readily seen using the Jones calculus. [44,48] This PB phase can be readily seen using the Jones calculus.…”
Section: Microlensesmentioning
confidence: 99%
See 3 more Smart Citations
“…[44,48] This PB phase can be readily seen using the Jones calculus. [44,48] This PB phase can be readily seen using the Jones calculus.…”
Section: Microlensesmentioning
confidence: 99%
“…It can be shown that when the thickness of the liquid crystal film is smaller than the characteristic length scale over which the PB phase varies by π, the incident (θ i ) and transmitted (θ t ) angle can be related to the PB phase Φ by the so-called generalized Snell's law [44] sin sin 2 The gradients of the PB phase cause the transmitted light to change its propagation direction.…”
Section: Microlensesmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of emerging applications become possible when spatially variant molecular orientation (also called molecular director) can be controlled at will. For example, liquid crystal Pancharatnam–Berry phase optical elements such as Q‐plates, lenses, and beam shapers can be made to modify the orbital angular momentum, propagation direction, and intensity profiles of light beams . The stimulus‐responsive deformations of liquid crystal elastomers can be preprogrammed in molecular director patterns, promising various applications in actuators and origami‐inspired surfaces .…”
mentioning
confidence: 99%